The orientation towards sports competition and its relationship to the Jerk performance for the first stage students in the College of Physical Education and Sports Science, University of Baghdad - Hussein, Hussein khmais; abdul khalik, Sajjad abdul wahid; Al- Ibraheemi, Dhafir Harb Ewajela (International Journal of Psychosocial Rehabilitation, 2020)
When a person has a strong motivation to obtain a goal, obtaining this goal that satisfies his motivation is considered as a reward that causes him a feeling of pleasure and contentment, and failure to obtain this goal is considered a type of punishment that causes him to feel pain or distress. The human being by his nature, tends to cause pleasure and avoids what causes him a pain, and for this reason, people naturally inclined to learn responses or actions that lead to success and avoid responses that lead to failure.